The predictive value of pretreatment hemoglobin-to-platelet ratio on osteoradionecrosis incidence rates of locally advanced nasopharyngeal cancer patients managed with concurrent chemoradiotherapy - Busra Yilmaz; Efsun Somay; Erkan Topkan; Ahmet Kucuk; Berrin Pehlivan; Ugur Selek (BMC, 2023)
Abstract Background This retrospective study aimed to investigate whether the pretreatment hemoglobin-to-platelet ratio (HPR) could predict the risk of osteoradionecrosis (ORN) in patients receiving concurrent chemoradiotherapy (C-CRT) for locally advanced nasopharyngeal carcinoma (LA-NPC). Methods ORN cases were reported from the records of LA-NPC patients who had oral examinations before and after C-CRT. The pretreatment HPR values were calculated on the first day of C-CRT. The connection between HPR values and ORN occurrences was determined using receiver operating characteristic curve analysis. The primary endpoint was the relationship between the pretreatment HPR values and post-C-CRT ORN incidence rates, while secondary endpoints included the identification of other putative ORN risk factors. Results We distinguished 10.9% incidences of ORN during the post-C-CRT follow-up period among 193 LA-NPC patients. The optimal cutoff for pre-C-CRT HPR was 0.48 that grouped the patients into two HPR groups with fundamentally different post-C-CRT ORN incidence rates: Group 1: HPR ≤ 0.48 (N = 60), and Group 2: HPR > 0.48 (N = 133). The comparative analysis indicated a significantly higher ORN incidence in HPR ≤ 0.48 group (30%; P < 0.001). The other factors associated with meaningfully increased ORN rates included the presence of pre-C-CRT ≥ 5 teeth extractions, mandibular volume receiving ≥ 64 Gy, post-C-CRT tooth extractions, mean mandibular dose ≥ 50.6 Gy, and C-CRT to tooth extraction interval > 5.5 months. Conclusion Low pretreatment HPR levels were independently and unequivocally linked to significantly increased incidence of ORN post-C-CRT. Pre-C-CRT HPR levels may be used to estimate the incidence of ORN and be useful for taking preventive and therapeutic measures in these patients such as monitoring oral hygiene with strict follow-up, avoidance of unnecessary tooth extractions, particularly after C-CRT, and use of more rigorous mandibular RT dose limits.